Model Pembelajaran Gamifikasi dalam Meningkatkan Motivasi Belajar Siswa Melalui Teknologi: Gamification Learning Model to Increase Student Motivation through Technology - Fajar Ayu, Amilia; Puspitasari, Asih; Hidayati, Nurin; Fitra Andikos, Adi (CV. Kalimasada Group, 2024)
This piece falls under the category of scholarly writing. It is a review of the literature, a type of scientific investigation that focuses on a particular subject. One of the ideas in e-learning is gamification. In the English language, it is frequently called